Millennial Fandom : Television Audiences in the Transmedia Age - Stein, Louisa Ellen (Book collections on Project MUSE., 2015)
"In an ambitious study encompassing a wide range of media texts, including popular television series like 'Kyle XY, ' 'Glee.' 'Gossip Girl, ' 'Veronica Mars, ' and 'Pretty Little Liars, ' and online works like 'The Lizzie Bennet Diaries, ' as well as fan texts from blog posts and tweets to remix videos, YouTube posts, and image-sharing streams, author Louisa Ellen Stein traces the circulation of the contradictory tropes of millennial hope and millennial noir. Looking at what millennials do with digital technology demonstrates the molding impact of commercial representations and at the same time reveals how millennials are undermining, negotiating, and changing those narratives"--Page 4 of cover.